Patterns of trade restrictiveness in online platforms: A first look. (16th October 2020) - Ferracane, Martina Francesca; van der Marel, Erik
Abstract: This paper develops a digital platform restrictiveness index for 64 countries based on ECIPE's Digital Trade Estimates database and the Digital Trade Restrictiveness Index. We identify specific restrictions that affect online platforms with a focus on online search, e‐commerce and social media. The results show that both OECD and non‐OECD countries show high levels of trade restrictions on online platforms. Moreover, some of the most restricted countries are characterised by large markets, signifying that a substantial part of the global economy gravitates towards restricting online platforms. Based on the platform restrictiveness index, we perform an econometric analysis showing that trade restrictions for online platforms are significantly associated with lower contributions of the ICT sector to productivity growth in the entire economy. The results suggest that reducing restrictions on online platforms can increase the ICT's contribution to overall productivity growth towards a level seen before the global financial crisis. Sectors that would benefit the most are those that make wider use of online platforms and the Internet, including information services, business services and financial services.